"Eat Your Greens": Increasing the Number of Days That Picky Toddlers Eat Vegetables. (June 2016) - Clason, Eiskje R.; Meijer, Denise
This article describes the development of a social marketing intervention, called "the vegetable box, " aimed at increasing the number of days per week that toddlers in the city of Rotterdam (the Netherlands) eat vegetables. The vegetable box tempts parents to offer vegetables as snacks and provides parents valuable insights on how to tempt their toddlers to give vegetables a try. This article presents the development of the vegetable box through a process of scoping, developing, implementing, evaluating, and follow-up. The vegetable box was evaluated by studying the effect, program, and process. The effect was evaluated by an experimental study with a pre- and posttest design and control group. Main results showed an increase in the number of days per week on which parents served vegetables and children ate them; surprisingly, though, the same result was found in the control condition. This was the first time that the present project team embarked on a social marketing journey. The article concludes with a description of the lessons learned.